The Influence of Feedback Environment Practices Established on School Practices in Kanowit Secondary Schools - Lim, Wee-Wee; Ling, Ying-Leh (Journal of Techno-Social, 2020)
This quantitative study aimed to determine the relationship of the feedback environment practices towards school climate. A total of 129 secondary schools’ teachers randomly from Kanowit district in Malaysia participated in the study. The results of the descriptive analysis showed that the level of the feedback environment practices based on the teachers’ perception is below-average. In terms of school climate, both collaboration and student relation dimensions have gained the above-average level while school resources dimension, decision-making dimension, and instructional innovation dimension have obtained the below-average level. Specifically, the study also found that the dimensions of feedback credibility, feedback quality, feedback delivery, and encourage feedback-seeking behaviour significantly influence on school climate. Therefore, organizational leaders must emphasize the existence of the feedback environment in the workplace as an injection into the school climate to ensure high performance among employees.